Comparative in vitro effects of novel and conventional parasiticides on Thaparocleidus vistulensis (Siwak, 1932) (Monopisthocotyla) parasitizing European catfish (Silurus glanis) - Wan Muhammad Hazim Wan Sajiri; Csaba Székely; István Czeglédi; Kurt Buchmann; Boglárka Sellyei (Aquaculture Reports)
This in vitro study compares the effects of the novel biological parasiticide Biokos (BIO) to the conventional anthelmintics Praziquantel (PZQ) and Mebendazole (MBZ) on the gill parasitic monopisthocotylan Thaparocleidus vistulensis (Siwak, 1932), a species-specific parasite of European catfish (Silurus glanis). Parasites were exposed to long-term treatment and tested at concentrations of 0, 1, 5, 10, 20, 40, 60, 80, and 100 mg/L. The antiparasitic effects were observed at all life cycle stages, including eggs, oncomiracidia, developing juvenile, and adult monopisthocotylans. In vitro assays demonstrated MBZ to be the most effective in inhibiting the development of eggs with 100 % efficacy. Treatment of BIO was proven effective in targeting the oncomiracidia life stage compared to the others. Higher concentrations are required for all antiparasitic treatments to show their effectiveness against developing juvenile and adult T. vistulensis. This suggests that strategic combinations of the parasiticides may elevate efficacy.